(untitled) (PIONIR: JURNAL PENDIDIKAN, 2025)
This research aims to determine the effect of problem-based learning models on elementary school students’ science self-efficacy. This study is a quasi-experimental study with a nonequivalent control group design using the Independent T-Test hypothesis test. The subjects of this study were 47 sixth grade students of SD Negeri 021 Sungai Kunjang. The research data were taken in qualitative form. The results of this study are the acquisition of students’ science self-efficacy scores in the experimental class, namely 208 in the pre-test, and 201 in the post-test, while in the control class, the pre-test score was 183, and the post-test was 181. The results of the hypothesis test showed a 2-tailed sig value of 0.406 (> 0.05) so that H0 was accepted and Ha was rejected. This is due to the limitations of the study and the complex concept of self-efficacy and requires long-term and consistent intervention, so that the impact can be seen more optimally. The dimensions of science self-efficacy also have a strong role in forming good SSE, so that the intervention given needs to pay attention to all dimensions evenly. Keywords: Problem Based Learning, Science Self Efficacy, Elementary School Students